1986
DOI: 10.1159/000118679
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization and Immunological Characterization of Vitamin D-Dependent Calcium-Binding Protein in the Bullfrog Cerebellum

Abstract: Antiserum prepared against rat renal calcium-binding protein (CaBP) was used with the unlabeled antibody peroxidase-antiperoxidase (PAP) technique to localize the 28,000 molecular weight CaBP in the cerebellum of the bullfrog, Rana catesbeiana. Whole brains of premetamorphic tadpoles and adults were fixed in Bouin's solution for 2 or 24 h and embedded in paraffin. 8-µm parasagittal sections were prepared and treated by the PAP method. Purkinje cells of the cerebellum in tadpoles and adults were specifically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Interestingly, the two-stage process of cerebellar development in the bullfrog appears to be an intriguing parallel to the findings on chick-quail chimeras, where the cerebellum differentiates from contributions of both metencephalic and mesencephalic regions [Martinez and Alvarado-Mallart, 1989;Hallonet et al, 1990;Alvarez-Otero et al, 1993]. Since vitamin D-dependent calcium binding protein (CaBP, calbindin) not only appears specifically in Purkinje cells of various animals such as chicks [Roth et al, 1981], rats [Legrand et al, 1983], and the bullfrog [Gona et al, 1986], but also at an early stage when the Purkinje cells are still bipolar, a CaBP immunocytochemical study of the ventral cerebellar region of the metamorphosing cerebellum in tadpoles is a particularly valuable tool to shed light on the pattern of distribution and maturation of the second wave of Purkinje cells.…”
Section: Introductionmentioning
confidence: 72%
“…Interestingly, the two-stage process of cerebellar development in the bullfrog appears to be an intriguing parallel to the findings on chick-quail chimeras, where the cerebellum differentiates from contributions of both metencephalic and mesencephalic regions [Martinez and Alvarado-Mallart, 1989;Hallonet et al, 1990;Alvarez-Otero et al, 1993]. Since vitamin D-dependent calcium binding protein (CaBP, calbindin) not only appears specifically in Purkinje cells of various animals such as chicks [Roth et al, 1981], rats [Legrand et al, 1983], and the bullfrog [Gona et al, 1986], but also at an early stage when the Purkinje cells are still bipolar, a CaBP immunocytochemical study of the ventral cerebellar region of the metamorphosing cerebellum in tadpoles is a particularly valuable tool to shed light on the pattern of distribution and maturation of the second wave of Purkinje cells.…”
Section: Introductionmentioning
confidence: 72%
“…In an earlier study, Gona et al [1986] observed CaBP immunoreactivity in mature Purkinje cells of the cerebellum in adults and tadpoles as well as in smaller cells in the auricular lobe region of tadpoles. The latter, small CaBP-immunoreactive cells were presumed to be immature Purkinje cells which were going to mature during metamorphosis.…”
Section: Introductionmentioning
confidence: 81%
“…Antibody to calbindin, the 28kDa calciumbinding protein that has been shown within the cerebellum to localize exclusively to Purkinje cells (Gona et al, 1986;Christakos et al, 1987) was used to verify the identity of the mutant Purkinje cells. Initial experiments were done with rabbit antisera from S. Christakos (Christakes et al, 1987), which was used at a primary antibody concentration of 1: 1000.…”
Section: Methodsmentioning
confidence: 99%